Characteristics of NtCCD1-3 from tobacco, and protein engineering of the CCD1 to enhance β-ionone production in yeast - Gong, Xiaowei; Li, Fan; Liang, Yupeng; Han, Xiulin; Wen, Mengliang (Frontiers in Microbiology, 2022)
Biosynthesis of β-ionone by microbial cell factories has become a promising way to obtain natural β-ionone. The catalytic activity of carotenoid cleavage dioxygenase 1 (CCD1) in cleavage of β-carotene to β-ionone severely limits its biosynthesis. In this study, NtCCD1-3 from Nicotiana tabacum with high ability to cleave β-carotene was screened. Multiple strategies for improving the β-ionone yield in Saccharomyces cerevisiae were performed. The results showed that NtCCD1-3 could cleave a variety of caroteniods at the 9,10 (9’,10’) double bonds and lycopene at the 5,6 (5’,6’) positions. The insertion site delta for NtCCD1-3 gene was more suitable for enhancing the yield of β-ionone, showing 19.1-fold increase compared with the rox1 site. More importantly, mutant K38A of NtCCD1-3 in membrane-bonding domains could greatly promote β-ionone production by more than 3-fold. We also found that overexpression of the NADH kinase Pos5 could improve β-ionone yield up to 1.5 times.These results may provide valuable references for biosynthesis of β-ionone.